The Effect of Taste and Temperature on Lingual Swallowing Pressure - Sandefur, Victoria (My University, 2019)
Swallowing is a complex sensorineural process that is affected by many components, one of which being the tongue. The tongue plays a crucial role in swallowing because it prepares and subsequently propels the bolus into the pharynx, initiating a swallow. It was hypothesized that the taste of a liquid would have an effect on the lingual pressure used in swallowing. This study used the Iowa Oral Performance Instrument (IOPI) to measure lingual pressure while the participant swallowed sweet, salty, bitter, and sour liquids. The lingual pressure in these trials was then examined against the participant’s baseline sample to determine the effectiveness of using different tasting liquids to elicit a more forceful swallow. Results for the control group and experimental group were compared to determine the impact of dysphagia on taste and lingual pressure.
I. INTRODUCTION. 1 -- II. LITERATURE REVIEW 2 -- Swallowing 2 -- The Muscles of the Tongue 5 -- Role of the Tongue in Swallowing 6 -- Age-Related Swallowing Changes 8 -- Dysphagia 9 -- The Effect of Taste on Swallowing 18 -- Purpose 21 -- Research Questions 22 -- Hypotheses. 22 -- III. METHODS AND PROCEDURES 23 -- Methods 23 -- Participants. 23 -- Procedures. 24 -- Measures. 24 -- Analysis 25 -- IV. 7RESULTS 2 -- 9-Point Hedonistic Scale Analysis 28 -- Lingual Pressure as a Function of Group and Taste 28 -- Lingual Pressure as a Function of Temperature 29 -- V. DISCUSSION 34 -- Relation of Data to Hypothesis 34 -- Interpretation 34 -- Implications. 35 -- Limitations. 36 -- Recommendations. 36 -- Conclusion. 37 -- REFERENCES 38 -- APPENDIX A: 9-Point Hedonic Scale 42 -- APPENDIX B: Intuitional Review Board. 44 -- APPENDIX C: IRB Participant Consent Form 47 -- APPENDIX D: Individual Participant Data 50.
Keywords: Academic theses; Speech therapy; Deglutition; Deglutition disorders